Efisien Dengan Strategi Tata Letak Gudang? Benarkah? - Lilik Darmawan; Basuki Basuki; Ginaris Aprianto; Ignatius Prasetya Aji Wibowo (Universitas Mercu Buana, 2021)
Abstract : PT. X Is a Trading Company that supplies promotional items such as glass, mugs, bowls, plates etc. Problems faced by PT. X is the condition of the pattern of preparation and storage of finished goods which are carried out randomly and less regularly resulting in difficulty in finding goods and the time taken to be longer. From these problems, this study discusses the planning of warehouse layout and storage of goods using the class based storage method. The study was conducted by examining 30 product items in order to find out the layout of goods based on ABC classification, the results show that of the 30 product items obtained grouping results into three classes, namely: 1) class A: 80% usage value with 11 items; 2) class B:use value of 15% with total items of 8 items and 3) class C:use value 5% with the number of item 11 items, the next stage classifying products using FSN analysis (Fast moving, Slow moving, Non moving) to find out and calculate the travel time carried out by warehouse workers in taking or storing goods. Based on research that has been done by comparing the initial layout and layout of proposal 1, it was found that the time reduction in the process of searching for goods storage locations was 529.3 minutes or 28.5% lower than the initial warehouse layout.